The development of strength through general and specific methods in kayaking and canoeing - Stojanovic, T.; Pasic, G.; Savic, Z. (Sports Science and Health, 2013)
With the development of canoe kayak sport (creating different disciplines and forms), and with a huge popularization of worldwide proportions, the competition is gorwing. Today's kayak canoe, along with athletics and swimming is the sport with the most participants and awarded medals (Peking, 2008 - 84 medals) in the Olympics. Trying to beat the opponents, athletes and their coaches use the experience of the other rowers. The constant dynamic of sport results progress is notable. With the use of knowledge in the field of medicine, physics, biomechanics and psychology, it is concluded, how much sports techniques and psychophysical skills are important for achieving superior results. Rowing and each discipline has its own peculiarities, where the development of certain forms of strength takes a special place. Among the endurance and speed, strength is the first among the equals. A variety of disciplines in the kayak canoe sport, required specialized competitors for each discipline. Major issues facing the profession and science are which forms of the power manifestation are essential in kayak canoe sport, their peculiarities, and which methods and exercises are for their development and improvemen